2006
DOI: 10.1016/j.eeh.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of New Deal expenditures on mobility during the Great Depression

Abstract: Using county-level data on federal New Deal expenditures on public works and relief and Agricultural Adjustment Administration payments to farmers, this paper empirically examines the New Deals impact on inter-county migration from 1930 to 1940. We construct a net-migration measure for each county as the difference between the Censuss reported population change from 1930 to 1940 and the natural increase in population (births minus infant deaths minus non-infant deaths) over the same period. Our empirical appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 43 publications
4
33
0
Order By: Relevance
“…Gutmann et al (2005; Gutmann and Field 2010; Deane and Gutmann 2003) have used Dust Bowl era population movements in developing explanations of the relationship between environment and American population trends more broadly, in giving context to the population displacements and migration that followed in the wake of 2005’s Hurricane Katrina, and as an inspiration for studying the relationship between dust storms and population change in later decades on the Great Plains. Fishback et al (2006) combined newly available economic datasets with census data to assess the effects of New Deal policies on migration, finding that areas of the US where larger amounts of money were spent on public works projects, relief, and agricultural assistance, were less likely to lose out-migrants and more likely to attract migrants from elsewhere. These findings echo qualitative evidence found by McLeman et al (2008) in eastern Oklahoma, which suggested that out-migration rates there would have been much higher if not for government assistance.…”
Section: Resultsmentioning
confidence: 99%
“…Gutmann et al (2005; Gutmann and Field 2010; Deane and Gutmann 2003) have used Dust Bowl era population movements in developing explanations of the relationship between environment and American population trends more broadly, in giving context to the population displacements and migration that followed in the wake of 2005’s Hurricane Katrina, and as an inspiration for studying the relationship between dust storms and population change in later decades on the Great Plains. Fishback et al (2006) combined newly available economic datasets with census data to assess the effects of New Deal policies on migration, finding that areas of the US where larger amounts of money were spent on public works projects, relief, and agricultural assistance, were less likely to lose out-migrants and more likely to attract migrants from elsewhere. These findings echo qualitative evidence found by McLeman et al (2008) in eastern Oklahoma, which suggested that out-migration rates there would have been much higher if not for government assistance.…”
Section: Resultsmentioning
confidence: 99%
“…Our focus is mostly on processes that are important for the less urbanized parts of the United States, where natural phenomena, such as precipitation and temperature, may have had a strong effect, either acting on their own or acting through agriculture, although we also include measures related to employment by industry and unemployment, which we hypothesize play a role in determining migration even in urban areas. While other researchers have examined the role of New Deal support programs in explaining migration (Fishback, Horrace et al 2006), our preliminary analysis suggested that they were less important than other factors, and they are not included in our statistical models.…”
Section: Understanding Relative Levels Of Out-migrationmentioning
confidence: 89%
“…In these approaches, a person’s likelihood of migrating is a function of his or her individual characteristics but also of the characteristics of their places of origin and destination, including the distribution of income, land, and human capital; the organization of agriculture and industry; public policy; and cultural frameworks, reflected in local ethnic, religious and racialconditions(Massey, Arango et al 1993, Fishback, Horrace et al 2006). Migration is also shaped by the structure of social networks.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Net migration under this method is equal to NetMig Survive t,t+10 = P op s t+10 −P op s t+10 . All data come from Ferrie (2003), except birth-death method estimates from 1930-1940 are from Fishback et al (2006).…”
Section: Calibration -The Role Of Changes In Labormentioning
confidence: 99%